2013
DOI: 10.1021/ml4003875
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Tertiary Amine and Indole Derivatives as Potent RORγt Inverse Agonists

Abstract: A novel series of tertiary amines as retinoid-related orphan receptor gamma-t (RORγt) inverse agonists was discovered through agonist/inverse agonist conversion. The level of RORγt inhibition can be enhanced by modulating the conformational disruption of H12 in RORγt LBD. Linker exploration and rational design led to the discovery of more potent indole-based RORγt inverse agonists.KEYWORDS: RORγt, agonists, inverse agonists, Th17 cell differentiation, cocrystal structure, structure-based design R etinoid-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 20 publications
4
70
0
Order By: Relevance
“…31 We previously showed that increasing size of a substituent on the phenyl ring of a tertiary amine RORt agonist could convert the agonist to an inverse agonist. 30 In this paper, it is the first time we observed that increasing size of a substituent on the phenyl ring of a thiazole ether RORt inverse agonist could convert the inverse agonist to an agonist.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…31 We previously showed that increasing size of a substituent on the phenyl ring of a tertiary amine RORt agonist could convert the agonist to an inverse agonist. 30 In this paper, it is the first time we observed that increasing size of a substituent on the phenyl ring of a thiazole ether RORt inverse agonist could convert the inverse agonist to an agonist.…”
Section: Resultsmentioning
confidence: 87%
“…27,28 RORt potency (pXC 50 ) and maximum response (%max) were measured in both FRET and dual FRET assays. 29,30 While the FRET assay is useful to identify antagonists, the dual FRET assay in which a surrogate agonist is not added allows the detection of both agonists and inverse agonists based on the changes in the basal level of RORt activity. 30 As we observed before, 27 addition of small alkyl groups such as Me (2a) and Et (2b) at 5-position of the thiazole ring did not change much of RORt activity in both FRET and dual FRET assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonsubstituted biphenyl amide 8a showed a RORγ Predicted binding mode of compound 4i (brown) and structural overlay with a previously published tertiary amine (blue) cocrystal structure with RORγt LBD using Surflex-Dock v2.3 in Sybyl 8.1. 37 FRET pIC 50 of 6.3. Adding a Cl group on ortho-position of the central phenyl ring (8b) enhanced RORγt activity.…”
mentioning
confidence: 99%